Association between prolonged P wave duration and left atrial scarring in patients with paroxysmal atrial fibrillation. (23rd July 2019) - Chen, Qiong; Mohanty, Sanghamitra; Trivedi, Chintan; Gianni, Carola; Della Rocca, Domenico G.; Canpolat, Ugur; Burkhardt, John David; Sanchez, Javier E.; Hranitzky, Patrick; Gallinghouse, Gerald Joseph; Al‐Ahmad, Amin; Horton, Rodney; et al.
Abstract: Background: We evaluated the association of P wave duration (PWD) with left atrial scar (LAS) in patients with paroxysmal atrial fibrillation (PAF). Methods: Consecutive patients with PAF undergoing their first catheter ablation were screened and only those in sinus rhythm at baseline were included in the analysis. A standard 12‐lead electrocardiogram (ECG) was performed in all and three‐dimensional voltage mapping of the left atrium was generated for identification of low‐voltage areas (≤0.2 mV) before the procedure. Results: In total, 411 patients with PAF were included in this study of which 181 had LASs (scar group), while 230 had no scar (nonscar group). In the scar group, patients were older (65.5 ± 8.8 vs 59.7 ± 11.7 years; P < .001), the proportion of female was higher (47.5% vs 37.4%; P = .04) and left atrial (LA) diameter (4.1 ± 0.6 vs 3.9 ± 0.6 cm; P < .001) was larger compared with the nonscar group. There was no significant difference in terms of hypertension, sleep apnea, and diabetes between the two groups. When comparing ECG characteristics between the two groups, PWD was significantly longer in the scar group (122.9 ± 18.5 and 116.9 ± 28.0 ms; P = .01). A multivariate analysis was performed, after adjustment of age, sex, LA diameter, PWD ≥ 120 ms was found to be an independent predictor of LA scarring (OR: 1.69, p ‐value: 0.02). Conclusion: In the current series, prolonged PWD was found to be independently associated with LA scarring in PAF, even after adjustment for age, sex, and LA diameter.